(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Faced economic units face the option of restoring the capital budget annually, and the information provided for the preparation of these budgets, including financial and non-financial aspects have an important impact in the numbers of these budgets, and these units differ in the ability of their own accounting systems to maintain this information. The aim of this research is to investigate the volume of accounting information that is relied on and the reasons for the differences between one unit and another in the various economic sectors in the Iraqi environment. The most important results of the research is the weakness of the adoption of decision makers in the Iraqi environment and lack of sufficient attention in the decision-making process.